From clinical bioethics to a global bioethics: thirty years of evolution - Gracia Guillén, Diego (Acta Bioethica, 2002)
Human Beings are respectable because they are Human Beings; not because they have the same worth or share the same beliefs. A new generation of human rights necessitates a new process of legitimization of political institutions. This is the essence of "Democracy and Bioethics". Life as we know it is under threat and from there emerges the importance of formulating a new table of human rights; ecological and environmental rights; the rights of different groups within society and the rights of future generations. These new rights are global and therefore demand a new type of democracy; it is this call for a global democracy, which must be discussed. Bioethics, in essence is a process of deliberation and discussion and therefore it is fitting that bioethics should provide the arena for discussion. It is important to realize that one day, deliberative democracy could be the reality, and be responsible for establishing a debate which reflects the diversity of ideas within society.